1996
DOI: 10.1016/0304-3959(96)03045-x
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic effect of subarachnoid neostigmine in two patients with cancer pain

Abstract: Two patients suffering with severe pain due to metastatic abdominal neoplasm were selected to examine whether subarachnoid neostigmine provided effective pain relief. Neostigmine was injected through a catheter introduced into the subarachnoid space at L4-L5. Patients were monitored for changes in arterial blood pressure, cardiac and respiratory rates, body temperature, level of consciousness and neurologic change. Pain was classified by the patients on a verbal four-grade scale, and analgesia was classified o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 5 publications
2
21
0
Order By: Relevance
“…11,[15][16][17][18] Spinal delivery of the cholinesterase inhibitor neostigmine inhibits the breakdown of the endogenous spinal neurotransmitter acetylcholine which has been shown to produce analgesia. [19][20][21] Neuraxial administration of neostigmine increases the concentration of acetylcholine in cerebrospinal fluid and produces antinociception in animals which is blocked by the intrathecal administration of a muscarinic antagonist.…”
Section: Objectifmentioning
confidence: 99%
See 1 more Smart Citation
“…11,[15][16][17][18] Spinal delivery of the cholinesterase inhibitor neostigmine inhibits the breakdown of the endogenous spinal neurotransmitter acetylcholine which has been shown to produce analgesia. [19][20][21] Neuraxial administration of neostigmine increases the concentration of acetylcholine in cerebrospinal fluid and produces antinociception in animals which is blocked by the intrathecal administration of a muscarinic antagonist.…”
Section: Objectifmentioning
confidence: 99%
“…[19][20][21] Neuraxial administration of neostigmine increases the concentration of acetylcholine in cerebrospinal fluid and produces antinociception in animals which is blocked by the intrathecal administration of a muscarinic antagonist. [15][16][17][18][19][20][21][22] The analgesic effect is thought to be mediated via spinal muscarinic M 1 receptors and supraspinal muscarinic M 1 and M 2 and nicotinic cholinergic receptors. 15,22 Autoradiographic studies 10.0 ± 2.1 9.8 ± 1.6 9.5 ± 1.6 9.7 ± 2.3…”
Section: Objectifmentioning
confidence: 99%
“…The intraspinal administration of neostigmine produces long-lasting analgesia in laboratory animals (1) and volunteers (14,15), and permits the management of both postoperative (16) and cancer pain (17). The antinociceptive effect of manipulating the central cholinergic system, however, seems to depend on the animal species and/or algesimetric assay utilized (see Ref.…”
Section: Introductionmentioning
confidence: 99%
“…1 Over 13 years of its clinical existence as intrathecal analgesic, Neostigmine has stood the test of time and has proven dose-dependent efficacy and good tolerability for both acute as well as chronic pain in dosage of 100-750 mg; most commonly used dosage for pain relief is 1-4 mg/kg body weight. 3,4,11 In our series, we used its 2 mg/kg body weight dose by epidural route and we found that Neostigmine provided good analgesic effect during rigid cystoscopy; median VAS pain score of 1 (range 0-3) compared to median 4 (range 3-7) in age-matched controls (P ¼ 0.0001). It has also been studied as adjunctive analgesic (dose of Neostigmine mentioned in parentheses) to various neuroaxially administered drugs, for example, lidocaine (1-4 mg/kg 19 ), intrathecal Bupivacaine (25-75 mg) 20 , epidural Ropivacaine (2-4 mg/kg), 21 and morphine (60 mg), 5 etc., and found to be useful in reducing drug dose, increasing analgesia duration, and decreasing opioid requirement.…”
Section: Discussion Analgesic Efficacy Of Neostigminementioning
confidence: 80%
“…1 After preclinical toxicity screening, the polar cholinesterase inhibitor, Neostigmine was introduced into clinical trials in 1995 for intrathecal injection 2 and has been found effective in chronic as well as postoperative pain. [3][4][5][6][7] Nausea and sedation are significant side effects of intrathecal administration of this drug which are uncommonly observed with epidural administration. 2,5 -8 Cholinergic side effects, for example, sweating, salivation, and abdominal cramping are exceedingly rare.…”
Section: Introductionmentioning
confidence: 99%